ADAPTATIONS OF DESERT PLANTS TO EXTREME ENVIRONMENTS - Mohammad shah Aadil Mir; Hina Ashraf Bhat (PT. Radja Intercontinental Publishing, 2023)
Desert plants are renowned for their ability to thrive in extreme environments characterized by limited water availability, high temperatures, and intense solar radiation. This paper explores the diverse adaptations that enable these plants to survive in such challenging conditions. Physiological adaptations, including water-use efficiency through CAM and C4 photosynthesis, along with morphological features such as reduced leaves and specialized root systems, play crucial roles in water conservation and heat tolerance. Behavioral adaptations, such as rapid germination and seed production following rainfall, further enhance their resilience. Understanding these adaptations not only illuminates the remarkable strategies of desert flora but also holds implications for ecological conservation and sustainable agriculture in arid regions.